PENGARUH PENGGUNAAN AI TOOLS DAN MOTIVASI KERJA TERHADAP KREATIVITAS FREELANCER GRAPHIC DESIGNER DI BALI - Gloria Dhida Sugiyanto; Gede Yudha Anugrah Pratama; Ni Komang Prasiani (STKIP Subang, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has fundamentally transformed the creative industry, including the way freelance graphic designers develop ideas and produce visual work. Beyond technological factors, work motivation has also been identified as a key determinant of individual creativity. This study aims to examine the effect of AI Tools usage on the creativity of freelance graphic designers in Bali, the effect of work motivation on their creativity, and the simultaneous effect of both variables. A quantitative approach with an explanatory research design was employed. Data were collected through an online questionnaire distributed to 165 freelance graphic designers belonging to the Bali Graphic Designer Facebook community, selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate that AI Tools usage has a positive and significant effect on creativity (t = 12.225; sig. = 0.000; β = 0.678), work motivation has a positive and significant effect on creativity (t = 3.209; sig. = 0.002; β = 0.178), and both variables simultaneously exert a significant effect on creativity (F = 121.011; sig. = 0.000), with an R Square value of 0.599. These findings suggest that the creativity of freelance graphic designers is shaped by the combination of AI-based technology utilization and individual motivational drive